Code-Mixing in Alternate Universe Story “Tjokorda Manggala” written by @guratkasih on Twitter - Rahmawati, Chatarina Tri (Humanis; Vol 26 No 4 (2022), 2022)
This research dealt with code-mixing phenomenon in the AU (alternate universe), that refers to fan fiction about one’s favorite celebrity. This type of fan fiction is mostly and largely published on Twitter as a social media platform. "Tjokorda Manggala," authored by @guratkasih, is one of several AUs with code-mixing in every tweet. This study delves deeper into the many sorts of code-mixing employed in "Tjokorda Manggala." It has been shown that 44 code-mixing occurrences were discovered from 28 tweets, with the kind of insertion (75%) being the highest or most usually employed. Alternation (9.1%) is only utilized in a few circumstances, while congruent lexicalization (15.9%) occurred more frequently than alternation. Some factors that caused code-mixing in the AU are settings and situations, participants, topics, and function of interaction. It is intended that through doing this research, the shift in linguistic patterns and how English has impacted Indonesians may be noticed, even in the realm of fan fiction.